Aortic calcifications and arterial stiffness as predictors of cardiovascular events in incident renal transplant recipients. (19th July 2013) - Claes, Kathleen J.; Heye, Sam; Bammens, Bert; Kuypers, Dirk R.; Meijers, Björn; Naesens, Maarten; Vanrenterghem, Yves; Evenepoel, Pieter
Summary: Renal transplant recipients have an increased risk of cardiovascular (CV) disease. Arterial stiffness (AS) and aortic calcifications (ACs) are well‐known CV risk factors in patients with chronic kidney disease. We aimed to determine the prognostic value of AS and AC in incident renal transplant recipients (RTRs). We conducted a prospective study in 253 single RTR. AC were scored by means of lumbar X‐ray. Carotid‐femoral pulse wave velocity (PWV) was assessed in a subgroup of 115 patients. AC were present in 61% of patients. After a mean follow‐up of 36 months, 32 CV events occurred in the overall group and 13 events in the PWV subgroup. When we accounted for age, gender, and CV history, AC score (HR, hazard ratio 1.09 per 1 unit increase; 95% CI 1.02–1.17) and PWV (HR 1.45 per 1 m/s; 95% CI 1.16–1.8) remained an independent predictor of CV events in Cox‐regression analyses. Using receiver operating characteristics, the area under the curve for predicting CV events amounted to 0.80 and 0.72 for sum AC and PWV, respectively. Both AS and AC are strong predictors of future CV events in an incident RTR population. These vascular assessments are readily available and easy to perform, making them ideal tools for further risk stratification. (ClinicalTrials.gov number: NCT00547040)